Maintaining exercise in fitness centre settings: insights from the physical activity maintenance theory - Luiz Fernando Santos Tross; Helton Magalhães Dias; Marcelo Callegari Zanetti (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This study examines factors that influence long-term fitness centre participation, applying the Physical Activity Maintenance Theory to assess psychological and contextual influences on exercise adherence. Methods Semi-structured interviews were conducted with 17 regular fitness centre attendees in Taubaté, São Paulo, Brazil. Data were analysed using Bardin’s Content Analysis, exploring the participants’ experiences and the factors contributing to their sustained activity. Results Autonomous motivation, such as enjoyment and satisfaction from workouts, along with self-efficacy, emerged as crucial for continued fitness centre attendance. The environment, including ambiance, social support, and facility quality, significantly impacted exercise persistence. However, challenges like time constraints, weather conditions, and personal issues occasionally hindered engagement. The study also highlights the role of personalized fitness programmes in supporting long-term adherence, suggesting that tailoring these programmes to individual goals could further enhance commitment. Conclusions The findings underscore the importance of fitness centres creating environments that align with individual needs and preferences. Customized programmes that cater to both personal and communal needs could bolster long-term adherence. Future research should explore the impact of personalized, community-integrated fitness approaches on sustaining active lifestyles, emphasizing the importance of accommodating individual preferences in maintaining regular exercise habits.